Semiotic Language Use in Schoolscapes on the Arctic Borderland - Outi Toropainen; Josefine Inga (Languages, 2024)
The article explores the visible, semiotic use of languages in two schoolscapes on the Arctic borderland and how these schoolscapes stimulate the learning of languages and cultures. The schools are situated in a historically multilingual area with several languages present. However, since the 17th century, the area has undergone Swedification, resulting in the current situation where all languages other than Swedish are endangered minority languages. The schoolscapes were studied through visual ethnography, and 229 photographs were analysed by qualitative content analysis. The results show that in one school in the middle of Sápmi, the Sámi languages were almost entirely excluded, despite their relevance and importance in maintaining bilingualism. Conversely, in a school where some pupils were from the Finnish side of the national border, the Finnish language was present in the form of various subject-relevant books. However, in both schools, all formal information is given to pupils in Swedish, with only a few exceptions permitted by the school management. Overall, the visual use of semiotic language is mainly teacher-produced, and the pupils’ opportunities to use the schoolscape as an affordance for active bilingualism through social participation are minimal.